The Study of Westward Drift in the Main Geomagnetic Field - G. Bayanjargal (International Journal of Geophysics)
We have obtained a solution for the velocity of westward drift from the induction equation in which an approach for main geomagnetic field was built. Distribution functions B(r, t) entered into the induction equation have been built by the observatories' data in North America and the Europe from 1991 to 2006. The longitudinal −0.123 degree/year and latitudinal 0.068 degree/year drifts were defined in North America. And the longitudinal −0.257 degree/year drift was defined in Europe from 1991 to 2006. These drifts are similar to results of other studies.